Student-Centered Empowerment of Teacher-centered Practices: An Action Research Project - Nicolas Clegorne; Roland Mitchell (Networks: An Online Journal for Teacher Research, 2013)
This action research reflects a narrative inquiry into the age-old debate concerning the relationship between theory and practice in educational settings. The unique perspective we add to this discussion is our distinct vantages. One researcher is a faculty member and the other is a student-affairs practitioner both working in a large public university. The insights we gleaned from this inquiry were drawn from our participant observation of a Foundations of Higher Education course. The course enrolled 22 students (many of whom worked full-time as student affairs practitioners) and we challenged them to engage theoretically dense material with the expressed aim of considering the connections between the class material and their day-to-day interactions as higher education practitioners.